Hubungan Antara Kepuasan akan Gaji, Kecerdasan Emosional dengan Komitmen Kerja - Khasanah, Uswatun; Aulia, Lailatuzzahro Al-Akhda (Fakultas Psikologi Universitas Yudharta Pasuruan, 2020)
Commitment is an attitude that reflects the extent to which an individual knows and is tied to his organization. The commitment of employees to their organization is an attitude that reflects the degree to which individuals are identified with and involved with the organization and do not wish to leave the organization. There are many factors that can affect employee work commitment, one of which is salary satisfaction and emotional intelligence. The hypothesis in this study is